Gambaran tingkat kecemasan pasien terhadap perawatan gigi tiruan lepasan akrilik (Kajian pada pasien prelansia dan lansia di RSGM-P FKG Universitas Trisakti) - Siti Fidra Suhendra; I Gusti Ayu Ratih Utari Mayun (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Tooth loss is a dental problem that often experienced by many people. One of the solutions to overcome cases of tooth loss is using acrylic removable denture. The long-term success of removable denture treatment is influenced by the adaptability of the patient. Anxiety can affect the patient's ability to adapt with the treatment received. Dental anxiety is one of the most common negative feelings experienced by patients when they go to the dentist for treatment. So it is necessary to evaluate the level of anxiety experienced by patients while receiving removable denture treatment. Objective: To evaluate the level of anxiety of patients who receive acrylic removable denture treatment at RSGM-P FKG Trisakti University. Method: This type of research is observational descriptive with a cross-sectional design. The study was conducted on 30 respondents who received acrylic removable denture treatment at RSGM-P FKG Trisakti University by distributing questionnaires using the interview method. Results: The results of the descriptive statistical test showed that the anxiety level of patients who received acrylic removable denture treatment was 20% not anxious, 73.3% mild anxiety, 3.3% moderate anxiety, 3.3% severe anxiety, and no one experienced extreme anxiety. In this study the level of anxiety that occurs in women is greater than that in men. Based on the age category, those aged 45-60 years experienced the highest level of anxiety, while those aged 75-90 experienced the lowest level of anxiety. Conclusion: The majority of the anxiety levels of patients who receive acrylic removable denture treatment at RSGM-P FKG Trisakti University are mild anxiety.